Anticancer agent ellipticine combined with histone deacetylase inhibitors, valproic acid and trichostatin A, is an effective DNA damage strategy in human neuroblastoma - Poljakova, Jitka; Hrebackova, Jana; Dvorakova, Marketa; Moserova, Michaela; Eckschlager, Tomas; Hrabeta, Jan; Göttlicherova, Marketa; Kopejtkova, Barbora; Frei, Eva; Kizek, Rene; Stiborova, Marie (Neuroendocrinology letters, 2011)
OBJECTIVES: Valproic acid (VPA) and trichostatin A (TSA) exert antitumor activity as histone deacetylase inhibitors, whereas ellipticine action is based mainly on DNA intercalation, inhibition of topoisomerase II and formation of cytochrome P450 (CYP)- and peroxidase-mediated covalent DNA adducts. This is the first report on the molecular mechanism of combined treatment of human neuroblastoma UKF-NB-3 and UKF-NB-4 cells with these compounds. - METHODS: HPLC with UV detection was employed for the separation and characterization of ellipticine metabolites formed by microsomes and peroxidases. Covalent DNA modifications by ellipticine in neuroblastoma cells and in incubations with microsomes and peroxidases were detected by 32P-postlabeling. Expression of CYP enzymes, peroxidases and cytochrome b5 was examined by Western blot. - RESULTS: The cytotoxicity of ellipticine to neuroblastomas was increased by pre-treating these cells with VPA or TSA. A higher sensitivity of cells to ellipticine correlated with an increase in formation of covalent ellipticine-derived DNA adducts in these cells. To evaluate the mechanisms of this finding, we investigated the modulation by VPA and TSA of CYP- and peroxidase-mediated ellipticine-derived DNA adduct formation in vitro. The effects of ellipticine in the presence of VPA and TSA on expression of CYPs and peroxidases relevant for ellipticine activation and levels of cytochrome b5 and P-glycoprotein in neuroblastoma cells were also investigated. Based on these studies, we attribute most of the enhancing effects of VPA and TSA on ellipticine cytotoxicity to enhanced ellipticine-DNA adduct formation caused by an increase in levels of cytochrome b5, CYP3A4 and CYP1A1 in neuroblastoma cells. A lower sensitivity of UKF-NB-4 cells to combined effects of ellipticine with VPA and TSA than of UKF-NB-3 cells is also attributable to high levels of P-glycoprotein expressed in this cell line. - CONCLUSION: The results found here warrant further studies and may help in the design of new protocols geared to the treatment of high risk neuroblastomas.